A new genus and species of Euphaeidae (Odonata, Zygoptera) from the early Eocene Okanagan Highlands locality at Republic, Washington, U.S.A. - Archibald, S. Bruce; Cannings, Robert A. (Zootaxa, 2021)
We describe Republica weatbrooki, a new genus and species of damselfly (Odonata, Zygoptera, Euphaeidae, Eodichromatinae) from the early Eocene (Ypresian) fossil locality at Republic, Washington, U.S.A. Its single specimen is the sole damselfly known from the Okanagan Highlands series of localities in far-western North America.